Diversity and Clinical Significance of Coagulase-negative Staphylococci: A Review of Identification, Virulence Factors & Drug Resistance - Sande, Suvarna (Pharmaceutical Science: New Insights and Developments Vol. 4, 2025)
Coagulase-negative Staphylococci (CoNS) are normal flora of human skin and mucous membranes, they have previously been considered nonpathogenic or contaminant having little clinical significance. CoNS are gram-positive, nonmotile, non-sporeforming cocci. CoNS have gained more importance as a pathogenic organism in recent years as a causative organism for infections in both humans and animals. CONS are mostly prevalent in immunocompromised patients, critically ill patients and patients having invasive medical devices. This study provides a comprehensive review of the understanding of microbiological profile, identification method and virulence factors associated with different Coagulase-Negative Staphylococci (CoNS) species. The incidence of CoNS varied across different geographic locations in humans and animals. Also, there are varying antibiotic resistance patterns observed in CoNS species, with high methicillin resistance and cross-resistance against many antibiotics. Staphylococcus epidermidis, Staphylococcus hemolyticus, Staphylococcus xylosus are the most commonly reported species in various studies. Various virulence factors in CONS are responsible for enhanced pathogenicity. In addition to virulence factors, the presence of many antibiotic-resistant genes found in CoNS is concerning and complicates treatment. Because of advancements in diagnostic techniques understanding of molecular mechanisms of CONS pathogenicity is possible. Recent advances in identification and typing methods and virulence screening methods will help to assess the true pathogenic potential of CoNS species. Future research should explore novel disinfection techniques, improved hand hygiene compliance strategies, and alternative antimicrobial agents to combat CoNS infection.